The role of induction chemotherapy in patients with locally advanced head and neck squamous cell carcinoma: A nationwide population-based matched study. (May 2022) - Hsieh, Meng-Che; Wang, Chih-Chun; Yang, Chuan-Chien; Lien, Ching-Feng; Wang, Chien-Chung; Shih, Yu-Chen; Yeh, Shyh-An; Hwang, Tzer-Zen
Highlights: For total population, survival were insignificant between induction chemotherapy and concurrent chemoradiotherapy. For patient with different primary tumor location, the role of induction chemotherapy was divergent. Induction chemotherapy had a positive impact on survival in patients with non-oral cavity cancers. Induction chemotherapy had a negative impact on survival in patients with oral cavity cancers. Primary tumor location should be taken into consideration during multidisciplinary team approach. Abstract: Introduction: Induction chemotherapy (IC) has a proven role in organ preservation and reducing distant failure. However, its ability to prolong survival remains controversy. Herein, our study aimed to investigate the impact of primary tumor location on survival in patients with locally advanced head and neck squamous cell carcinoma (LA-HNSCC) treated with IC. Methods: Patients who were older than 18 years and diagnosed with LA-HNSCC between 2007 and 2016 were retrospectively identified from Taiwan National Health Insurance Research Database and Taiwan Cancer Registry. Patients were categorized into two group: IC group and CCRT group. In order to reduce the selection bias, IC patients were individually matched with the CCRT patients. The oncologic outcomes were presented with overall survival (OS). Results: A total of 5547 patients were identified. After matching, 2208 patients were analyzed for outcomes comparison, including 1104 patients in each group. In general, median OS were 27.3 months versus 28.5 months in IC and CCRT group, respectively (p = 0.6151). Patients were stratified by primary tumor location. For patients with oral cavity cancers, the median OS was significantly inferior in IC group than those in CCRT group, while for patients with non-oral cavity cancer, the median OS was superior in IC group than those in CCRT group. Conclusions: Primary tumor location has a significant impact on survival in patients with LA-HNSCC treated with IC. Our study provides a strong evidence that primary tumor location should be taken into consideration during multidisciplinary approach.